CUPROPHAN VE POLİSÜLFON DİALİZÖRLERİNİN OKSİDAN /ANTİOKSİDAN DENGESİ ÜZERİNE ETKİLERİ - SEYMEN, Pınar; SEYMEN, H. Oktay; ÖZDEMİR, Ali and BELCE, Ahmet and GÜMÜŞTAŞ, Koray and TÜRKMEN, Funda and ÖZEL BARUT, Yıldız (Cerrahpaşa Medical Journal, 2014)
Background and Design.- In chronic renal insufficiency, many toxic metabolites which are normally nontoxic but become toxic when combined improving oxidative metabolism, accumulates in the body fluids. We studied the effect of the most frequently used cuprophan and polysulfone dialysers in hemodialysis treatment on oxidant/antioxidant status. For this purpose, 26 cases (9 females, 17 males, mean age of 36) that are used cuprophan dialysers (n=15) and polysulfone dialysers (n=ll) were examined. The cases with COPD, DM and the ones using vitamin E and C, were excluded. First the plasma and red blood cells of the venous blood taken before and after hemodialyses were separated and than plasma MDA and intraerythrocyter GSH levels, activities of GSH-Px and SOD were measured. Results.- When the groups that are used cuprophan and polisulfone dialysers are compared; It is observed that the cuprophan dialysers increased plasma MDA levels (p<0.05), decreased the intraerythrocyter GSH levels (p<0.01), activities of GSH-Px (p<0.05) and SOD (p<0.05), as polisulfone dialysers did not influence the MDA and GSH levels, activities of GSH-Px and SOD (p>0.05). Conclusion.- Hemodialysis treatment is an oxidant stress for the organism and some of used dialysers is effective on this oxidant stress. As a conclusion, this is important in developing new membranes to control the production of free oxygen radicals.